2017
DOI: 10.1371/journal.pone.0176948
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the greenhouse gas emissions of Brazilian soybean biodiesel production

Abstract: Soybean biodiesel (B100) has been playing an important role in Brazilian energy matrix towards the national bio-based economy. Greenhouse gas (GHG) emissions is the most widely used indicator for assessing the environmental sustainability of biodiesels and received particular attention among decision makers in business and politics, as well as consumers. Former studies have been mainly focused on the GHG emissions from the soybean cultivation, excluding other stages of the biodiesel production. Here, we presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 37 publications
0
9
0
1
Order By: Relevance
“…Donald et al 2006;Raven and Wagner 2021). We found that soybean (the most important source of biodiesel in Brazil, one of the world's largest biodiesel producers (Cerri et al 2017)) severely reduced local biodiversity, more so than other row crops including maize (Fargione et al 2010;Poggio et al 2013). Yet maize and wheat were still very damaging compared to primary and secondary vegetation and second-generation biofuels, reflecting the homogeneity and limited resource availability in row crop landscapes (Smith et al 2010).…”
Section: Discussionmentioning
confidence: 92%
“…Donald et al 2006;Raven and Wagner 2021). We found that soybean (the most important source of biodiesel in Brazil, one of the world's largest biodiesel producers (Cerri et al 2017)) severely reduced local biodiversity, more so than other row crops including maize (Fargione et al 2010;Poggio et al 2013). Yet maize and wheat were still very damaging compared to primary and secondary vegetation and second-generation biofuels, reflecting the homogeneity and limited resource availability in row crop landscapes (Smith et al 2010).…”
Section: Discussionmentioning
confidence: 92%
“…The selection and development of biomass is a crucial, cost-limiting phase in biofuels generation for adjusting and optimizing energy structure and cost. Selection of biomass for biofuels production is also directly related to greenhouse gas emissions, environmental and economic sustainability [ 12 ]. The current focus is on microalgae as a feedstock for bioenergy production as the most promising raw material to compensate and balance the ever-increasing demands for biofuels, food, feed and valuable chemicals production [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…• GHG emissions attributed to 1 kg soy bean meal: in literature values varying from 0.4 kg (Mogensen, 2011), 0.5 kg (Zgola et al, 2016), 0.7kg (Cerri et al, 2017;Dalgaard et al, 2008) are found (all excluding post-harvest transport; differences due to region of sourcing, and whether or not to include land-use-change effects in consideration). Transport to Europe may add up to 0.4 kg CO2-eq.…”
Section: Ghg Emissions Analysismentioning
confidence: 99%